2010
DOI: 10.1590/s0104-56872010000400021
|View full text |Cite
|
Sign up to set email alerts
|

Correlação entre voz e fala traqueoesofágica e pressão intraluminal da transição faringoesofágica

Abstract: TEMA: reabilitação do laringectomizado total. OBJETIVO: correlacionar a proficiência de voz e de fala de laringectomizados totais usuários de prótese traqueoesofágica com a pressão intraluminal da transição faringoesofágica no repouso e durante a fonação. MÉTODO: foram estudados 12 laringectomizados totais com voz traqueoesofágica, usuários de prótese fonatória, submetidos à coleta e registro do material de voz e da fala, que foram avaliados por três expertos, utilizando-se um protocolo de julgamento geral da … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Speech therapy is included in publications on the treatment of laryngeal cancer, in studies dealing with rehabilitation of functions related to communications (in this case, especially oral communication) [22][23][24][25][26][27] , evaluation of quality of life 9,12,25,[28][29][30] , swallowing rehabilitation 9,28,30 and alterations of smell and taste 31 . During the research it was also verified a considerable percentage of publications from the nursing sector related with the bio-psycho-social aspects directly linked to the rehabilitation and/or postoperative handling/care which the patients must be submitted to [32][33][34][35][36][37][38][39] .…”
Section: Series Of Casesmentioning
confidence: 99%
“…Speech therapy is included in publications on the treatment of laryngeal cancer, in studies dealing with rehabilitation of functions related to communications (in this case, especially oral communication) [22][23][24][25][26][27] , evaluation of quality of life 9,12,25,[28][29][30] , swallowing rehabilitation 9,28,30 and alterations of smell and taste 31 . During the research it was also verified a considerable percentage of publications from the nursing sector related with the bio-psycho-social aspects directly linked to the rehabilitation and/or postoperative handling/care which the patients must be submitted to [32][33][34][35][36][37][38][39] .…”
Section: Series Of Casesmentioning
confidence: 99%
“…Although esophageal and TE speech differ from each other and clearly differ from that of normal speech production, the aerodynamic capacity and trans-pseudoglottal flows and pressure are greater during TE speech [8][9][10][20][21][22]28,29]. In comparing TE, esophageal, and normal speakers on acoustical characteristics of fundamental frequency, intensity, and duration, Robbins et al [9] found that TE speech was characterized as having the greatest intensity, a higher frequency than esophageal speakers, and finally, temporal features that approximated normal speakers.…”
Section: Introductionmentioning
confidence: 99%
“…That is, TE speakers' access to pulmonary air may help them generate increased airflows and associated air pressures within the vocal tract during TE speech production. However, an additional concern in this context rests with the fact that TE speakers do not have an adductor-abductor voicing mechanism; rather, the response of the postlaryngectomy vibratory source may in many respects be somewhat passive despite increased driving pressures secondary to the access to lung air by these speakers [20][21][22]. Data reported in the literature support this assumption [9].…”
Section: Introductionmentioning
confidence: 99%